2020
DOI: 10.1787/457c263d-en
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging tourism development for sustainable and inclusive growth in South Africa

Abstract: This document, as well as any data and map included herein, are without prejudice to the status of or sovereignty over any territory, to the delimitation of international frontiers and boundaries and to the name of any territory, city or area. 2  ECO/WKP(2020)29 Unclassified OECD Working Papers should not be reported as representing the official views of the OECD or of its member countries. The opinions expressed and arguments employed are those of the author(s). Working Papers describe preliminary results or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Sustaining healthy wild animal populations is particularly important for South Africa whose rural economy is reliant on ecotourism (Snyman, 2014), an industry which relies on biodiversity and key mega-fauna such as the "Big Five" that include lion and leopard, to maintain tourism that contribute to South Africa's GDP in a meaningful way and reach the national target to become one of the top 50 destinations worldwide (Glocker and Haxton, 2020). While there may be no direct link between wild animal use for traditional medicine and depleting populations of wildlife in South Africa, practitioners in our study reported that lion, vulture, leopard, python, eland, hippo, and mole have increased in rarity or become unavailable over the last 5 years.…”
Section: Potential Risksmentioning
confidence: 99%
“…Sustaining healthy wild animal populations is particularly important for South Africa whose rural economy is reliant on ecotourism (Snyman, 2014), an industry which relies on biodiversity and key mega-fauna such as the "Big Five" that include lion and leopard, to maintain tourism that contribute to South Africa's GDP in a meaningful way and reach the national target to become one of the top 50 destinations worldwide (Glocker and Haxton, 2020). While there may be no direct link between wild animal use for traditional medicine and depleting populations of wildlife in South Africa, practitioners in our study reported that lion, vulture, leopard, python, eland, hippo, and mole have increased in rarity or become unavailable over the last 5 years.…”
Section: Potential Risksmentioning
confidence: 99%